CRB-65 for risk stratification and prediction of prognosis in pulmonary embolism - Keller, Karsten; Schmitt, Volker H.; Sagoschen, Ingo; Münzel, Thomas; Espinola-Klein, Christine; Hobohm, Lukas (Journal of Clinical Medicine, 2023)
Background: Pulmonary embolism (PE) is accompanied by high morbidity and mortality. The search for simple and easily assessable risk stratification scores with favourable effectiveness is still ongoing, and prognostic performance of the CRB-65 score in PE might promising. Methods: The German nationwide inpatient sample was used for this study. All patient cases of patients with PE in Germany 2005-2020 were included and stratified for CRB-65 risk class: low-risk group (CRB-65-score 0 points) vs. high-risk group (CRB-65-score ≥1 points). Results: Overall, 1,373,145 patient cases of patients with PE (76.6% aged ≥65 years, 47.0% females) were included. Among these, 1,051,244 patient cases (76.6%) were classified as high-risk according to CRB-65 score (≥1 points). The majority of high-risk patients according to CRB-65 score were females (55.8%). Additionally, high-risk patients according to CRB-65 score showed an aggravated comorbidity profile with increased Charlson comorbidity index (5.0 [IQR 4.0-7.0] vs. 2.0 [0.0-3.0], p < 0.001). In-hospital case fatality (19.0% vs. 3.4%, p < 0.001) and MACCE (22.4% vs. 5.1%, p < 0.001) occurred distinctly more often in PE patients of the high-risk group according to CRB-65 score (≥1 points) compared to the low-risk group (= 0 points). The CRB-65 high-risk class was independently associated with in-hospital death (OR 5.53 [95%CI 5.40-5.65], p < 0.001) as well as MACCE (OR 4.31 [95%CI 4.23-4.40], p < 0.001). Conclusions: Risk stratification with CRB-65 score was helpful for identifying PE patients being at higher risk of adverse in-hospital events. The high-risk class according to CRB-65 score (≥1 points) was independently associated with a 5.5-fold increased occurrence of in-hospital death.
Gesehen am 31.03.2023